Mathematical modelling of the immune response to infectious diseases with the influence of environmental factors - Yaroslav Bihun; Oleh Ukrainets (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The mathematical model of the immune response to infectious diseases with the influences of environmental factors is investigated. The conditions for the existence and uniqueness of the solution to the mathematical model for t>0 have been  established. Stationary solutions have been identified, along with the conditions for their existence and asymptotic stability. The results are illustrated using a model example.